Differences by Gender in Predictors of Motivation Among Substance Abuse Treatment Participants. (21st March 2017) - Taylor, Liana R.; Caudy, Michael; Blasko, Brandy L.; Taxman, Faye S.
ABSTRACT: Background : Substance-involved females tend to have different clinical profiles than men (Adams, Leukefeld, & Peden, 2008 ); yet they do not appear to have worse treatment outcomes (Green, 2006 ; Hser, Huang, Teruya, & Anglin, 2003 ). As motivation for treatment is considered essential in the substance abuse treatment context (Cahill, Adinoff, Hosig, Muller, & Pulliam, 2003 ; Longshore & Teruya, 2006 ), it is possible that higher motivation among females could potentially counteract the negative effect of more risk factors. Objective : The purpose of the current study was to examine if females differ from males in their motivation for treatment using the Texas Christian University Motivation Form scales: desire for help, problem recognition, treatment readiness, pressure for treatment, and treatment needs; and whether factors predicting motivation for treatment differed between male and female participants of substance abuse treatment. Methods : The sample included 2, 989 substance-involved males and 982 substance-involved females who were referred to substance abuse treatment through a case management program. Linear regression models predicting each motivation scale were analyzed, followed by gender-specific models. Results : Overall, the results did not demonstrate a significant gender difference in the motivation scales. However, among male participants, the findings did show that Hispanic significantly predicted desire for help and alcohol as a primary drug of choice predicted treatment readiness. Conclusion : Findings suggest that motivation for treatment may be a gender-neutral construct, and that there is a need to better understand sociodemographic predictors of motivation.